The origins of Tshivenda: an archaeological challenge to historical linguistics - Huffman, Thomas N. (Southern African Humanities, 2022)
From an archaeological perspective, the Venda language, Tshivenda, evolved in the past 500 years in northern South Africa, rather than 1500 years ago as some historical linguists claim. The archaeological record for the past 500 years in the Limpopo Valley clarifies the cultural processes involved in this evolution. The ceramic record there for Sotho (Icon pottery) and Kalanga (Khami pottery) documents interaction between the two groups, facilitated by Kalanga initiation schools for males and females held in chiefs’ and headmen’s settlements placed along the ethnic boundary. Male circumcision took place in the bush. These schools helped to create Tshivenda and Venda cultural identity. The transformation was not limited to the Mapungubwe landscape, however, and interaction shaped by formal initiatory rites, notably domba, most likely occurred throughout Venda. The sequence of linguistic changes was complete by the time the Singo established the Venda nation in the 18th century. Archaeological evidence indicates that Tshivenda was the product of convergence.